Exaggerated T‐wave alternans in children with Angelman syndrome - Eleonora Tamilia; Navaneethakrishna Makaram; Georgios Ntolkeras; Assia Chericoni; Sebastian Holst; Joerg Hipp; Alexander Rotenberg (Annals of the Child Neurology Society)
Abstract Objective We aimed to test whether T‐wave alternans (TWA), which is a marker of susceptibility to ventricular fibrillation, is abnormal in children with Angelman syndrome (AS) compared with typically developing children (TDC), and whether it can be used as a biomarker of AS. Materials and Methods Using surface electrocardiogram (ECG), we calculated TWA in AS and compared it between AS and TDC (Wilcoxon rank sum test). We then performed logistic regression to test TWA ability to distinguish AS from TDC. Results We observed higher TWA in AS than TDC (44 vs. 33 uV, p = 0.009), while heart rate did not differ (p = 0.26), nor its variability (p = 0.72). TWA values enabled discrimination between AS and TDC (p = 0.0008) with accuracy of 81%, positive predictive value of 72%, and negative predictive value of 100%. Interpretation Our findings suggest that ECG in children with AS contains evidence of acquired cardiac abnormality via pathologically increased TWA.